Visual Media Development of Wayang Culture Based on 2D Object Motion using Kinect Sensor - Awang Pradana; Syaiful Nugraha; Salya Rater (LPPM Politeknik Aceh Selatan, 2022)
One of the works of art inherited by the ancestors of the Indonesian state, which is most in demand by the public is wayang art, which comes from folklore or fairytale. This concern for preserving the art of wayang, which is a characteristic of Javanese regional traditions, is an important factor in preserving the history of folklore, especially in Indonesia. However, preserving the wayang art culture is not easy, sometimes there are difficulties or obstacles in learning how to introduce the art of wayang to early childhood. In this new technological the use of art can be mediated or cast through interaction in the digital world. Inseparable from the concept of a system being developed at the time, one of the system concepts uses interaction technology for motion detection or motion sensors to detect.Microsoft introduced the Kinect sensor on gaming consoles in the Xbox retail package. Therefore, researchers use these sensors with the existence of these sensors and use the field of artistic graphic interaction to digitally manipulate 2D image forms.Creation of simulations in digital form using the C# programming language and several openCV (Open Source Computer Vision) tools. It is hoped that in the future this visualization can be used by parents to introduce their children to the art of wayang culture, so that children can learn about some of the characters in wayang art at an early age.